Association Between Maternal Hyperglycemia and Composite Maternal-Birth Outcomes - Shen, Song-Ying; Zhang, Li-Fang; He, Jian-Rong; Lu, Jin-Hua; Chen, Nian-Nian; Xiao, Wan-Qing; Yuan, Ming-Yang; Xia, Hui-Min; Lam, Kin Bong Hubert; Qiu, Xiu (Frontiers in Endocrinology, 2018)
Objective: The overall impact of maternal hyperglycemia on maternal and birth outcomes is largely underestimated, therefore quantifying the true burden of hyperglycemia in a whole population it is a challenging task. This study aims at examining the association between blood glucose concentration during pregnancy and a composite score of adverse maternal-birth outcomes in a large-scale prospective cohort study in China. Methods: Pregnant women within “the Born in Guangzhou Cohort Study”, China who underwent a standard 75-g oral-glucose-tolerance-test (OGTT) between 22 and 28 gestational weeks were included. A composite score of stillbirth, duration of pregnancy, birth weight, preeclampsia, and cesarean section was developed based on a published maternal-fetal outcomes scale, weighed by the relative severity of the outcomes. Multiple linear regression models were used to assess the associations between OGTT glucose measurements and log composite score. Logistic regression models were used to assess relations with outcome as a categorical variable (0, 1-<3 and ≥3). Findings: Among 12129 pregnancies, the composite score ranged from 0 to 100 with a median of 2.5 for non-zero values. Elevated fasting glucose level was associated with higher composite score (adjusted coefficients 0.03 [95% CI, 0.02-0.04] for 1-SD increase). For 1-SD increase in fasting glucose, the risk of having a composite score 1-<3 and ≥3 rises by 13% (95% CI, 8%-17%) and 15% (95% CI, 7%-23%), respectively. Similar association and increase in risk was found for 1-hour and 2-hour glucose. Conclusion: Elevated fasting, 1-hour, and 2-hour glucose levels are associated with a range of adverse maternal-birth outcomes. The composite score model can be applied to the risk assessment for individual pregnant women and to evaluate the benefits for controlling glucose levels in the population.